Preparation and thermal properties of form-stable phase change materials composed of palmitic acid/polypyrrole/graphene nanoplatelets - Silakhori M.; Fauzi H.; Mahmoudian M.R.; Metselaar H.S.C.; Mahlia T.M.I.; Khanlou H.M. (Elsevier Ltd, 2023)
Dye-sensitized solar cells; Energy storage; Graphene; Heat storage; Palmitic acid; Saturated fatty acids; Solar energy; Thermal conductivity; Thermal energy; Thermodynamic properties; Conductivity analysis; Form stable phase change material; Graphene nanoplatelets; Nano-platelets; SEM analysis; Solar thermal energy; Ultra-sonication; Phase change materials